2016
DOI: 10.1007/s41465-016-0003-2
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Brain Stimulation and Neural Entrainment Enhance Athletic Performance—a Review

Abstract: Brain stimulation and neural entrainment relying on noninvasive techniques, applied to sports, might enhance brain activity in healthy athletes to improve their physical performance. In the past, several studies have employed stimulation procedures, either during athletic training or during separate sessions, to enhance physical and mental performance. Here, we review the available physiological and behavioral studies to clarify if and under which conditions noninvasive brain stimulation and neural entrainment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 40 publications
1
45
0
2
Order By: Relevance
“…Beyond NFB training, there are other methods to improve skills and motor performance based on neuroplasticity 38,39,40 . Non-invasive brain stimulation (NIBS) techniques facilitate motor skill learning by increasing the corticospinal excitability.…”
Section: Psychophysiological Interventions: Bio-neurofeedback and Tramentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond NFB training, there are other methods to improve skills and motor performance based on neuroplasticity 38,39,40 . Non-invasive brain stimulation (NIBS) techniques facilitate motor skill learning by increasing the corticospinal excitability.…”
Section: Psychophysiological Interventions: Bio-neurofeedback and Tramentioning
confidence: 99%
“…Evidence from recent studies suggests links between tDCS induced corticospinal excitability, skill learning, and motor performance 40 . In a golf putting task, it was shown that tDCS applied over the left side of prefrontal cortex facilitates implicit motor learning.…”
Section: Psychophysiological Interventions: Bio-neurofeedback and Tramentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in neuroscience suggest that sports performance can be enhanced by using methods and techniques that modify brain activity, thus leading to the improvement of athletes' mental state and focus, as well as encouraging motor learning (Vargo et al, 2014). Recently, the potential and effectiveness of noninvasive brain stimulation techniques (i.e., neuroscientific intervention techniques, able to safely induce neuromodulation or neurostimulation effects on cortical structures and networks)-and of combined neurofeedback and mental training programs for pursuing such goals and for optimizing athletes' cognitive and behavioral performances-have been more and more explicitly explored (Balconi, Fronda, Venturella, & Crivelli, 2017;Balconi, Pala, Crivelli, & Milone, 2019;Borducchi et al, 2016;Colzato, Nitsche, & Kibele, 2017;Crivelli, Fronda, Venturella, & Balconi, 2019;Davis, 2013;Lewthwaite & Wulf, 2017). While the attention given to potential applications of noninvasive stimulation and neuromodulation techniques likely followed the need for novel models and methods for intervention and the will to try and overcome limitations and ethical issues raised by first tentative neuroenhancement approaches based on chemicals and psychoactive drugs, it has to be acknowledged that such potential and its practicalethical implications in the field of sports practice is still a matter of debate.…”
Section: Neuroscientific Techniques For Sports Performance Enhancementmentioning
confidence: 99%
“…Lastly, Colzato et al (2017) suggest that brain stimulation techniques seem to be useful in fine-tuning crucial aspects of competitive sports such as speeding up the learning rate of specific motor skills.…”
mentioning
confidence: 99%